Improving Descriptive Text Writing Skills of 7th Grade Students of SMP Al Karomah Peterongan with Picture and Picture Learning Model - Zamzamie, Nabiel; Rokhmansyah, Alfian (Jurnal Ilmu Manajemen dan Pendidikan, 2024)
The aim of this study was to improve the descriptive writing skills of 7th-grade students at Al Karamah Junior High School using the picture and picture learning model. The research method used was classroom action research, conducted in two cycles including planning, action implementation, analysis, and reflection. The study involved 26 7th-grade students at Al Karamah Junior High School. The findings showed that the picture and picture learning model significantly enhanced the students' ability to write descriptive texts from the pre-cycle stage to cycle I and from cycle I to cycle II. The study concluded that the picture and picture learning model effectively enhance the descriptive writing skills of 7th-grade students at Al Karamah Junior High School, with students showing improved work quality and achievement, increasing from 26% before the intervention to 33% in cycle I and 88% in cycle II.